Analysis and Dynamic Behavior of Portal Structure Due Rotating Machines Loads - Donald Essen; Luqyana Luqyana (Journal of Applied Science, Engineering, Technology, and Education, 2019)
Rotating machines can be regarded as live load when the machine is operating at a period of time at a certain speed will result in vibration on the structure. The purpose of this research to perform dynamic analysis of the portal structure in order to know how much influence the dynamic load due to the machine that is operating on the structure and get a large ratio of displacement, velocity, and acceleration when the load is given a static and dynamic load. This dynamic analysis is done with the help of SAP2000 V.20.0.2 software. From the results of this study, it was found that the first ten shape modes of the structure did not experience resonance, although in a third mode natural frequency obtained at 57.466 Hz which has a result of 0.865 Hz and is said to be close to resonance, but the frequency does not have much impact on the structure. In addition to considering the resonance value, the structure also considers the value of all amplitudes and the results of the internal forces of the structure. From the results of the amplitude of displacement, velocity, and acceleration shows that vibration does not affect humans and does not damage the structure in accordance with applicable regulations and standards.